An Assessment of Land Use and Land Cover Change for Lubovane Reservoir Sub-Catchment in Eswatini - Mamba, M. P.; Mkhonta, S. V.; Vilane, B. R. T.; Mkhwanazi, M. M.; Hlanze, D. K. (European Journal of Applied Sciences, 2023)
The increasing population in rural areas, increased livestock densities and extensive deforestation have been reported as the main drivers of land degradation in Eswatini. Land degradation, along with biodiversity loss and climate change presents serious challenges to the environment, economy and the country’s development agenda. This study was conducted to assess the land use land cover (LULC) changes within the Lubovane reservoir catchment. Landsat 4-5 TM images were used for mapping LULC changes for 1995, 2000, 2005, 2009 and a Landsat 8 image was used for mapping 2015 LULC. A supervised LULC classification was conducted using 6 classes (water, settlements, irrigation, cultivation, shrubs and forests, as well as bare land) in ArcGIS version 10.3.1. The classification was validated using a confusion matrix and the results reflected that water, irrigation, cultivation, forests and shrubs were well classified. The LULC assessment results indicated that there was low coverage of water bodies observed from 1996 – 2005, while a 3% increase was observed in 2009. Water coverage decreased to 1.9% in 2015 due to the El-Niño induced drought that hit Southern Africa, resulting in low inflow to the dam. A reduction of shrubs and forest cover was experienced in 2000 due to conversion of forested areas into settlements for resettled households. However, a slight increment of shrubs and forest was observed from 2009 to 2015. A reduction in the concentration of forests cover around the reservoir, an increase of settlements and bare land were also observed.